Robot‐assisted laparoscopic ureteric reimplantation: extravesical technique. (14th August 2014) - Dangle, Pankaj P.; Shah, Anup; Gundeti, Mohan S.
<x xml:space="preserve">Abstract</x> Objectives To describe our standardised approach to performing robot‐assisted extravesical ureteric reimplantation. Patients and Methods A total of 29 children, with high grade (III–V) vesico‐ureteric reflux (VUR) underwent robot‐assisted extravesical ureteric reimplantation between September 2010 and September 2013. Follow‐up renal ultrasonography was performed at 1 month and 3 months and a voiding cysto‐urethrogram (VCUG) was obtained at 4 months to assess VUR resolution. Results The mean (range) patient age at the time of surgery was 5.38 (3.0–10.0) years. Postoperative VCUG showed complete resolution of VUR in 32/40 ureters (80%). Of the remaining refluxing ureters, downgrading of VUR on VCUG was shown in 7/8 ureters (87.5%). The mean (range) length of hospital stay was 1.8 (1–3) days. Conclusions In conclusion, robot‐assisted extravesical ureteric reimplantation is technically feasible with acceptable resolution of VUR.